Body Mass Index among Nepali Soldiers Serving in the Peacekeeping Mission of the United Nations: A Pre and Post Deployment Comparative Study - Khadka, Sitaram; Thapa, Raj Kumar; Sharma, Arun; Subba, Rama; KC, Kanchan; Luitel, Asmita (Medical Journal of Shree Birendra Hospital, 2025)
Introduction: Body mass index is a crucial anthropometric tool for the assessment of body composition and cardiovascular risk factors. Maintaining body mass index is essential to everyone including soldiers for preventing chronic diseases and promoting overall health. This study was conducted to evaluate the body mass index of Nepali soldiers deployed inthe United Nations Peacekeeping Mission to support their fitness and well-being. Methods: A one-year longitudinal follow-up study was conducted among 351 Nepali soldiers deployed at the United Nations Disengagement Observer Force, Syria from November 2021 to November 2022. Body mass index was categorized based on the Centers for Disease Control and Prevention guidelines and the association between demographic variables and body mass index was determined using a chi-square test. Results: Only 40.46% of the soldiers maintained their body mass index at the normal level. Body mass index changed slightly over the year from 19.27 to 31.62 kg/m² on day 1 to 18.80–33.10 kg/m² on day 365, with a significant association between units, height, weight, and body mass index category. The decreasing trend of body mass index was evident at the officers’ rank whereas it was found to increase at other ranks. Conclusions: The increasing trend of body mass index among soldiers, except officer rank, indicates the need for regular monitoring and intervention from educational, nutritional, and psychological aspects for the fitness of soldiers in United Nations Peacekeeping Missions. Similar types of interventions are needed throughout the tenure of soldiers, at their unit, as well.